05Jan

помогииииите дам 20 б

Kol1an Алгебра 2 13

помогииииите дам 20 б

Posted by Kol1an | Posted at Jan 05, 2014 | Categories: Алгебра

Answers

Ингир
Ингир

[latex] dfrac{ sqrt{9 + a^2 - 6a} }{a - 3 } = dfrac{ sqrt{(a - 3)^2} }{a - 3 } = dfrac{|a - 3|}{a - 3 } = dfrac{|2,5 - 3|}{2,5 - 3} = dfrac{0,5}{-0,5} = -1 [/latex] Ответ: -1. 

Jan 05, 2014 07:39
Puet49
Puet49

[latex] sqrt{(9+a^2-6a)} /(a-3)= sqrt{(a-3)^2} /(a-3)=|a-3|/(a-3)=[/latex][latex]|2,5-3|/(2,5-3)=0,5/(-0,5)=-1[/latex]

Jan 05, 2014 07:41

Leave a answer